Valoración económica del secuestro de CO2 en un bosque de teraza baja del distrito de Maquía, Loreto - 2020 - Ramos Derteano, Fiorella Alessandra (2021)
The economic value of the commercial timber volume was compared with the value of the CO2 sequestration service in a low-terrace forest in the Maquía district, Loreto, Peru. The forest census data of commercial species from PC 1 of the forest concession contract for timber purposes was evaluated. The results indicate that the economic value of timber amounts to USD 376 649,30. In addition, the species P. cladantha (USD 55 464,45), C. guianensis (USD 40 655,07), B. reticulata (USD 36 327,82) and O. puberula (USD 35 766,12); Together they are the ones that report the highest economic value in the study area. The economic value of CO2 sequestration reports USD 1 086 371,28. Likewise, the species P. cladantha (USD 142 211,60), A. decandra (USD 139 053,51), C. guianensis (USD 125 657,36) and B. reticulata (USD 109 801,82) are the species with the highest economic value; while V. venulosa (USD 3160,07) and V. pavonis (USD 2022,40) reported lower value. When contrasting the net profit from the sale of roundwood with the economic value of CO2 sequestration in the evaluated forest, a difference in favor of the CO2 sequestration service of USD 553 302,78 is noted.